The Practice of Dhaif Hadith in the Community - Herdiyana Herdiyana; Munir Munir (Gunung Djati Conference Series, 2021)
This study aims to determine the hadith dhaif and know the practice of hadith dhaif in the community, this research is a qualitative type with a description of the analysis and historical approach then collects data findings in the form of secondary and primary. The results of this study are to know the meaning of dhaif hadith both in language and terms, to know the rules that exist in the practice of dhaif hadith, to know examples of dhaif hadiths and their syarah, to know the kinds of dhaif hadiths, especially those spread in the community, to know the kinds of dhaif hadiths, and know the form of practice of dhaif hadith in society. This research results in the fact that there are hadiths that are weak in the sanad or matan, and it turns out that there are several conditions so that we can practice the dhaif hadith with certain conditions, even a lot of attention from scholars regarding this dhaif hadith. This study recommends that there be research, especially field surveys by analyzing so that it is more precise.